ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MP-ASI DINI DI KELURAHAN ARCAWINANGUN KECAMATAN PURWOKERTO TIMUR 1 TAHUN 2014 - Feti Kumala Dewi; Melati Khusnanisa (Universitas Harapan Bangsa Purwokerto, 2014)
0-6 months old mother stated that 7 <35 years of providing complementary foods such as honey,porridge sun, bananas (5 mothers with low education (elementary, middle), 4 work and 6 hadrevenue> Rp. 1,000,000, -), and three mothers aged> 35 years did not give breast milk (oneworking mother, two highly educated mothers, and one mother had revenue> Rp. 1,000,000, -).The purpose of this study to describe age, education, occupation, economic status of mothers andthe provision of complementary feeding and to know the relationship, age, education, employmentand economic status of women with early breast milk giving dikelurahan Arcawinangun work areaPuskesmas East Purwokerto 1 2014.This research method is analytical correlation with cross sectional approach based on primarydata. This research instrument with a checklist. Sempelnya are mothers with babies aged 0-6months. Sempel retrieval technique is cluster sampling with a sample of 30 respondents.The result of this research is the most maternal age is â‰¤ 35 years (60%). Based on the highest levelof education is low (63.3%). Most are based on the work of working mothers (56.7%). Based onthe economic status of the mother is the most economic high (53.3%) and the provision of thehighest breast milk is not suitable (â‰¤ 6 months), namely (66.7%). There was no associationbetween maternal age with early administration of MP-ASI with Ï value 0.461. There is arelationship between the mother's education by giving breast milk to premature Ï value 0,001.There is a relationship between the mother's occupation by giving breast milk to premature Ïvalue 0,007.There is no correlation between economic status women with early breast milk givingthe value Ï 0.122. Keywords: Age, Education, Employment, Economic Status, MP-ASI